Evaluating ecological outcomes from environmental stewardship initiatives: A comparative analysis of approaches. (1st November 2021) - Baird, Julia; Plummer, Ryan; Jollineau, Marilyne; Dale, Gillian
Abstract: Understanding the extent to which stewardship initiatives achieve objectives of enhanced ecological outcomes is important for enhancing effectiveness and efficiency of environmental management initiatives. Alternative approaches – community science, stakeholder perceptions, and remote sensing - are emerging in lieu of the conventional approach of collecting field data that present different benefits and drawbacks and to date have not been directly compared. This research compared the use of four approaches to evaluating ecological outcomes of a grassland restoration project on a 2 ha Niagara Parks Commission property in Ontario, Canada. We collected three levels of quantitative data, from general site assessments to species-specific data using standardized questionnaires and multi-spectral imagery from a remotely piloted aircraft system. We found that community scientists and stakeholders provided comparable general site assessments to the field data, but that as the assessments became more detailed, differences emerged. Further, remotely sensed data were assessed and provided a more positive site assessment than any other method. Experiences and knowledge of nature did not influence assessments by community scientists or stakeholders. Our findings show that for overall site assessments, community scientists and stakeholders may be able to provide a reasonably accurate assessment. If monitoring and evaluation needs (either research-based or practical) extend beyond a broad assessment, use of a field expert or multiple methods of data collection may be warranted. Highlights: The broadest site assessments showed the greatest agreement among approaches. As assessments became more specific, differences among approaches emerged. Community science and stakeholder approaches performed poorly at the species level. Assessment of remote sensing data resulted in overestimations of site health.